Penerapan Model Pembelajaran Project Based Learning (PjBL) untuk Meningkatkan Hasil Belajar Siswa Pada Muatan IPA Kelas IV SD - Israwaty, Ila; Mukhlisa, Nurul; Bahar, Bahar; Salsabila, Intan (Universitas Negeri Makassar, 2023)
This study objectives to improve students learning processes and students achievement in science content of grade IV UPT SD Negeri 2 Rappang. Qualitative research approach with the type of classroom action research (PTK). The implementation of the action consists of planning, implementation, observation, and reflection. The percentage level of the process and student learning achievement is known through the results of observation sheets and evaluation tests in each cycle. The subjects of this research are teachers and grade IV students in the 2022/2023 school year totaling 20 students. The results of the first cycle research on the teacher aspect obtained C qualifications, the student aspect C qualifications, and the results of the student evaluation test C qualifications. The results of the implementation of cycle II on the teacher aspect obtained qualification B, the student aspect qualification B, and the results of the student evaluation test qualification B. The conclusion of this research is that by applying the Project Based Learning (PjBL) learning model can improve the process and learning achievement of students in the science content of grade IV UPT SD Negeri 2 Rappang.